An Anterior Cruciate Ligament In Vitro Rupture Model Based on Clinical Imaging. Issue 9 (July 2021) - Willinger, Lukas; Athwal, Kiron K.; Williams, Andy; Amis, Andrew A.
Background: Biomechanical studies on anterior cruciate ligament (ACL) injuries and reconstructions are based on ACL transection instead of realistic injury trauma. Purpose: To replicate an ACL injury in vitro and compare the laxity that occurs with that after an isolated ACL transection injury before and after ACL reconstruction. Study Design: Controlled laboratory study. Methods: Nine paired knees were ACL injured or ACL transected. For ACL injury, knees were mounted in a rig that imposed tibial anterior translation at 1000 mm/min to rupture the ACL at 22.5° of flexion, 5° of internal rotation, and 710 N of joint compressive force, replicating data published on clinical bone bruise locations. In contralateral knees, the ACL was transected arthroscopically at midsubstance. Both groups had ACL reconstruction with bone–patellar tendon–bone graft. Native, ACL-deficient, and reconstructed knee laxities were measured in a kinematics rig from 0° to 100° of flexion with optical tracking: anterior tibial translation (ATT), internal rotation (IR), anterolateral (ATT + IR), and pivot shift (IR + valgus). Results: The ACL ruptured at 26 ± 5 mm of ATT and 1550 ± 620 N of force (mean ± SD) with an audible spring-back tibiofemoral impact with 5 o of valgus. ACL injury and transection increased ATT ( P < .001). ACL injury caused greater ATT than ACL transection by 1.4 mm (range, 0.4-2.2 mm; P = .033). IR increased significantly in ACL-injured knees between 0° and 30° of flexion and in ACL transection knees from 0° to 20° of flexion. ATT during the ATT + IR maneuver was increased by ACL injury between 0° and 80° and after ACL transection between 0° and 60°. Residual laxity persisted after ACL reconstruction from 0° to 40° after ACL injury and from 0° to 20° in the ACL transection knees. ACL deficiency increased ATT and IR in the pivot-shift test ( P < .001). The ATT in the pivot-shift increased significantly at 0° to 20° after ACL transection and 0° to 50° after ACL injury, and this persisted across 0° to 20° and 0° to 40° after ACL reconstruction. Conclusion: This study developed an ACL injury model in vitro that replicated clinical ACL injury as evidenced by bone bruise patterns. ACL injury caused larger increases of laxity than ACL transection, likely because of damage to adjacent tissues; these differences often persisted after ACL reconstruction. Clinical Relevance: This in vitro model created more realistic ACL injuries than surgical transection, facilitating future evaluation of ACL reconstruction techniques.